Angiogenic Factor Imbalance Early in Pregnancy Predicts Adverse Outcomes in Patients With Lupus and Antiphospholipid Antibodies: Results of the PROMISSE Study. Issue 4 (December 2016) - Kim, M.Y.; Buyon, J.P.; Guerra, M.M.; Rana, S.; Zhang, D.; Laskin, C.A.; Petri, M.; Lockshin, M.D.; Sammaritano, L.R.; Branch, D.W.; Porter, T.F.; Merrill, J.T.; et al.
Abstract : ( Am J Obstet Gynecol . 2016;214:108.e1–e.14) Systemic lupus erythematosus (SLE) predominantly affects women and commonly presents during their childbearing years. Pregnancy in patients with SLE, particularly those with antiphospholipid (APL) antibodies, and in patients with APL alone, is associated with an increased risk for maternal and fetal morbidity due to preeclampsia (PE) and insufficient placental support of the developing fetus. PE and placental insufficiency are, in turn, associated with adverse pregnancy outcomes (APOs), including maternal complications of PE, intrauterine fetal death, and fetal growth restriction, as well as indicated preterm delivery. Hence the ability to identify patients who are destined for poor outcomes, early in pregnancy, would significantly impact care of this high-risk population.